Percepatan Penulisan Karya Ilmiah Guru melalui Workshop Penggunaan ChatGPT dan Perplexity di Pondok Pesantren - Efriyanti, Liza; Derta, Sarwo; Annas, Firdaus (Jurnal Solusi Masyarakat (JSM), 2024)
One of the challenges faced by educators is the preparation of scientific papers, particularly in regard to the structure, content, and time required for completion. To address this challenge, a workshop on accelerating teachers' scientific writing through the use of ChatGPT and Perplexity was conducted at Pondok Pesantren Mu'alimin Kamang Magek, West Sumatra. The objective of this activity is to assist educators in enhancing their scientific writing abilities with the aid of artificial intelligence (AI) technology. The implementation method employed a blended learning approach, wherein participants received hands-on guidance in the utilization of ChatGPT for brainstorming and drafting, as well as Perplexity for the enhancement of text readability and coherence. The results of the workshop demonstrated a notable enhancement in participants' abilities, with 80% of them exhibiting the capacity to construct a more structured outline. The utilization of ChatGPT facilitated the writing process, whereas Perplexity enhanced the quality of the text. Consequently, it can be concluded that this workshop is an efficacious strategy for augmenting teachers' scientific writing productivity. It is, therefore, recommended that it be conducted on a regular basis with the provision of online assistance as a follow-up measure.